PENERAPAN METODE ROLE PLAY TERHADAP KONEKSI MATEMATIS SISWA KELAS IV SEKOLAH DASAR - Fadilah, Ayu Syifa Putri; Rahmawati, Ery; Susilo, Tri Achmad Budi (Universitas Tanjungpura, 2023)
This study aims to determine the implementation of the Role Play learning method on the mathematical connection of fourth grade students at SD Pomosda Tanjunganom Nganjuk. The research method used is quantitative, specifically quasi-experimental. The quasi-experimental was chosen based on the consideration that in the implementation of this research learning took place naturally, and students did not feel experimented. The subjects of this study were 30 Pomosda fourth grade elementary school students consisting of 13 girls and 17 boys. While the instruments used are documentation sheets, observation sheets, and test sheets. From this study, it was found that there was a significant increase in the results of the pretest and posttest. In the pretest the average value is 38, while in the posttest it is 74. For the N-gain result, 0.58 is included in the medium criteria. In the learning process, the avarge result is 79,4% which is good. The conclusion of this research is the role play method can improve mathematical connection in fourth grade students of SD Pomosda in learning mathematics. The role play method has been successful in elementary schools but not necessarily successful for higher levels. For this reason, research on the implementation of role play for learning Mathematics in secondary schools needs to be carried out.